Uji Aktivitas Antioksidan Fraksi n-Heksan dan Etil Asetat Daun Kelor (Moringa oleifera) - Taufik; Haeruddin; Nurlansi (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2023)
Research has been done Antioxidant Activity Test of n-Hexane and Ethyl Acetate Fractions of Moringa Leaves (Moringa oleifera). The aim of this study for knowing what types of secondary metabolites are contained in the n-hexane and ethyl acetate fractions as well as the antioxidant activity of the n-hexane and ethyl acetate fractions of Moringa leaves. The secondary metabolites contained in the n-hexane and ethyl acetate fractions of Moringa leaves were determined by the phytochemical method, while the antioxidant activity was tested by the DPPH method. Leaf Moringa used is dried Moringa leaves that have been mashed. From 500 grams of finely powdered Moringa leaves (Moringa oleifera), macerated with 2,000 mL methanol for 3x24 hours, obtained as much as 139.57 grams of methanol thick extract. Then proceed with fractionation using the liquid-liquid partition method. As much 30 grams of macerated methanol viscous extract is dissolved in 100 mL of distilled water. The solution was then partitioned by adding 100 mL of n-hexane, shaken in a separating funnel and allowed to stand until there are two layers. The distilled water layer was re-partitioned with ethyl acetate in the same way and evaporated so that obtained n-hexane fraction as much as 1.88 grams and 1.66 grams of ethyl acetate. Phytochemical test results showed that the n-hexane fraction contained alkaloids, steroids and saponins. While the ethyl acetate fraction contains alkaloids, steroids, saponins, tannins and polyphenols. The results showed that the n-hexane fraction mhas antioxidant activity which is classified as very weak with an IC50 value of 299.80 ppm and the ethyl acetate fraction have strong antioxidant activity with an IC50 value of 57.98 ppm.